A Contrastive Analysis of Compliment Strategies and Compliment Responses Strategies on Native Javanese and Non-Native Javanese Learners of English - Br.Sinulingga, Desi Rahma Yuni; Setia, Eddy; Mono, Umar; Lubis, Syahron; Rangkuti, Rahmadsyah (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
English learners may be influenced by culture when giving and responding to compliments. This is because they learn language through culture. In this study, tribes have different compliment response strategies. That is why cross-cultural variations cannot be ignored in terms of pragmatics. The aim of this research is to analyze the similarities and differences of compliment strategies and compliment response strategies to see the effect of culture on NJ and NNJ when giving and responding to compliments. This research is a contrastive analysis and uses qualitative methods. The data used are the answers of the participants contained in the questionnaire. The participants are 10 speakers, 5 native Javanese (NJ) and 5 non-native Javanese speakers learning English (NNJ) from 1st, 2nd, and 3rd students of English Postgraduate Program using questionnaires and interviews as research instruments. The findings of this research show that NJ and NNJ are "partly correspondence" in terms of compliment strategies and compliment responses strategies. The results of the research on compliments and responses show that NJ and NNJ use some of the same strategies but differ in the frequency of their use. Then, the research results on compliment responses show that acceptance with amendment: comment and non-acceptance: avoidance are the most frequently used by NJ, while acceptance: appreciation token is the most frequently used by NNJ. The results shows that NJ tended to adopt Javanese culture, which is characterized by "andhop ashor" or humility, while NNJ adopted Western culture, which is more expressive and direct.